2021
DOI: 10.3390/v13040570
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Regarding Hantavirus Detection in Rodent Tissue Samples and Urine

Abstract: The natural hosts of Orthohantaviruses are rodents, soricomorphs and bats, and it is well known that they may cause serious or even fatal diseases among humans worldwide. The virus is persistent among animals and it is shed via urine, saliva and feces throughout the entirety of their lives. We aim to identify the effectiveness of hantavirus detection in rodent tissue samples and urine originating from naturally infected rodents. Initially, animals were trapped at five distinct locations throughout the Transdan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The main transmission routes of hantaviruses are usually direct contact with rodents or inhalation of contaminated aerosols from excretions or secretions of infected animals ( 16 ). Most of the studies to date have reported hantaviruses in lung and kidney samples from rodents ( 17 , 18 ), with only a few studies focusing on hantaviruses in other organs, such as the liver ( 1 , 19 ). A recent study reported the detection of Dobrava–Belgrade virus, Puumala virus, and Tula virus in liver tissue samples from Apodemus, Myodes , and Microtus rodent species in Hungary ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main transmission routes of hantaviruses are usually direct contact with rodents or inhalation of contaminated aerosols from excretions or secretions of infected animals ( 16 ). Most of the studies to date have reported hantaviruses in lung and kidney samples from rodents ( 17 , 18 ), with only a few studies focusing on hantaviruses in other organs, such as the liver ( 1 , 19 ). A recent study reported the detection of Dobrava–Belgrade virus, Puumala virus, and Tula virus in liver tissue samples from Apodemus, Myodes , and Microtus rodent species in Hungary ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies to date have reported hantaviruses in lung and kidney samples from rodents ( 17 , 18 ), with only a few studies focusing on hantaviruses in other organs, such as the liver ( 1 , 19 ). A recent study reported the detection of Dobrava–Belgrade virus, Puumala virus, and Tula virus in liver tissue samples from Apodemus, Myodes , and Microtus rodent species in Hungary ( 19 ). SEOV has been detected in liver tissue samples from feeder rats in the Netherlands and from wild R. norvegicus in New York ( 1 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…After dissection, the harvested organ specimens were preserved at −80 °C until further analysis. Tissue RNA was extracted from the homogenate of the kidney, the organ where mammarenaviruses, orthohantaviruses and orthonairoviruses are highly prevalent, as described in previous viral surveillance studies [17, 19–21]. Briefly, kidney tissue was shredded with scissors and homogenized in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…However, the life-long persistence of hantaviruses in tissues and excreta is unclear due to the varying results obtained from previous studies on hantavirus pathogenesis and virus shedding in experimentally infected natural hosts with Hantaan, Puumala or Seoul orthohantavirus strains [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%